Biallelic SCN2A Gene Mutation Causing Early Infantile Epileptic Encephalopathy: Case Report and Review - AlSaif, Shahad (J Cent Nerv Syst Dis, 2019)
The voltage-gated sodium channel neuronal type 2 alpha subunit (Na(v)α1.2) encoded by the SCN2A gene causes early infantile epileptic encephalopathy (EIEE) inherited in an autosomal dominant manner. Clinically, it has variable presentations, ranging from benign familial infantile seizures (BFIS) to severe EIEE. Diagnosis is achieved through molecular DNA testing of the SCN2A gene. Herein, we report on a 30-month-old Saudi girl who presented on the fourth day of life with EIEE, normal brain magnetic resonance imaging (MRI), normal electroencephalography (EEG), and well-controlled seizures. Genetic investigation revealed a novel homozygous missense mutation (c.5242A > G; p.Asn1748Asp) in the SCN2A gene (NM_001040142.1). This is the first reported autosomal recessive inheritance of a disease allele in the SCN2A and therefore expands the molecular and inheritance spectrum of the SCN2A gene defects.